2004
DOI: 10.1007/s11910-004-0024-6
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumor cerebri

Abstract: Pseudotumor cerebri (PTC) is a syndrome of increased intracranial pressure without hydrocephalus or mass lesion and with normal cerebrospinal fluid (CSF) composition. Although often considered to be "idiopathic," detailed investigation has revealed a high incidence of venous outflow abnormalities in PTC syndrome patients. The thought that elevated intracranial venous sinus pressure is a "universal mechanism" for PTC syndrome of varying etiologies has been called into question by a study indicating that the inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 51 publications
3
23
0
Order By: Relevance
“…6 Even if it is assumed that venous stenosis exists in PTC, there is controversy as to whether venous stenosis and elevated venous pressure are due to elevated ICP or constitute the proximal cause of PTC. [14][15][16] The first explanation is an application of the Monroe-Kellie doctrine: Expansion of the brain within a fixed space will lead to the compression of venous sinuses, assuming that these are compressible structures, to vent CSF during systole when ICP increases. 17 One cadaveric study suggested that the stenosis of the transverse sinus observed in IIH might be due to the presence of a large septum within the venous sinus.…”
Section: Etiologymentioning
confidence: 99%
See 3 more Smart Citations
“…6 Even if it is assumed that venous stenosis exists in PTC, there is controversy as to whether venous stenosis and elevated venous pressure are due to elevated ICP or constitute the proximal cause of PTC. [14][15][16] The first explanation is an application of the Monroe-Kellie doctrine: Expansion of the brain within a fixed space will lead to the compression of venous sinuses, assuming that these are compressible structures, to vent CSF during systole when ICP increases. 17 One cadaveric study suggested that the stenosis of the transverse sinus observed in IIH might be due to the presence of a large septum within the venous sinus.…”
Section: Etiologymentioning
confidence: 99%
“…15 A small or absent bony groove in the occiput in conjunction with the compressible nature of the transverse sinus makes this structure vulnerable to tapering with increased ICP. 65 This particular imaging finding is more frequently noticed on MR venography studies, which are discussed at more length below.…”
Section: Mr Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…Surgical procedures like optic nerve sheath fenestration and lumboperitoneal or ventriculoperitoneal shunting may improve the venous drainage from the brain [6,8,15]. Since IIH is associated with venous sinus hypertension, venous sinus stenting has also been proposed for unresponsive cases [16]. Of these procedures, optic nerve sheath fenestration requires less anesthesia time which is one of the factors that has to be considered in pregnant women [3].…”
Section: Discussionmentioning
confidence: 99%